Impact Des Facteurs De Pollution Sur La Qualite Des Eaux De La Zone Aval De La Vallee De L’oued Nekor (Al-Hoceima, Maroc) - Dimane, Fouad; Haboubi, Khadija; Hanafi, Issam; El Himri, Abdelouahad; Andaloussi, Kaouthar (European Scientific Journal, ESJ, 2017)
Water is a precious and essential natural resource for multiple uses. Its use for food or hygiene requires excellent physicochemical and microbiological quality. To assess the quality of well water for human consumption in the Al Hoceima region which is located in North of Morocco, a physico-chemical and bacteriological control was carried out on the basis of 10 water samples from wells in this area. The analyzes were performed on these samples by measuring the following physic-chemical parameters: temperature, pH, electric conductivity (EC), chloride (Cl -),dissolved oxygen, nitrate (NO3 -), and possibly seeking unwanted bacteria (total bacteria, total coliforms, fecal coliforms, fecal streptococci). The samples were analyzed systematically to measure all the physicochemical indicators of pollution. Correlation between pollution parameters were conducted to give a reponse element on the main causes pollution. The results performed analysis, revealed a pollution of an agricultural origin. This is confirmed by the maximum levels of chlorides, which exceed 2640 mg/l, thereby explaining the high conductivity levels (4800μs/cm). In addition 14% of analyzed wells have nitre levels 50mg/l nitrate pollution a not alarming. However, if a pollution of agricultural origin is mentioned, the lithological contribution can not be neglected on the results obtained.